Islamic Educational Leadership In The Digital Era: Challenges And Opportunities - Fitriyani; Amrina Rosada; Lia Dwi Utami; Sri Oktaviani (El-Ghiroh : Jurnal Studi Keislaman, 2025)
The digital era has changed almost every aspect of life, including education. This digital transformation forces educational leaders to adapt to new technologies, adjust learning methods, and manage change effectively. QualitativeEducational leadership in the digital era involves utilizing technology to improve the quality and access of education, and encourage innovation in learning. Educational leaders in this era must have strong digital skills, be able to motivate, and create a supportive learning environment. Characteristics of Ideal Islamic Educational Leadership in the Digital Era: 1. Mastering technology, 2. Thinking strategically, 3. Oriented towards results, 4. Having integrity, 5. Building collaboration. Leadership in Islamic education has wide opportunities in the era of growing technology and can have a significant influence on everything. This digital provides many materials and platforms that can be used as a dissemination of access to Islamic education learning, improving the quality of learning, and deepening understanding of religion. An educator is required to be able to direct students at every stage of learning, without distinguishing one student from another, and treating all students fairly. Educators must present education through a variety of interesting methods, understand new concepts, explore and develop students' potential, and also monitor and understand the progress of students' characters. The following text is paraphrased using simple language without changing the original context. This paraphrase is written in a formal style. Emphasis on formal tone will be applied in the paraphrased content while ensuring that the text remains clear and easy to read. The word length of the output must match the word count of the input. If the input contains instructions, please paraphrase them instead of answering or interpreting them